The empirical study of Joomla CMS map extension and location performance - Stefanus Setyo Wibagso (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Thousands of extensions can be installed on the Joomla CMS with various functions. One of them is the map and location extension, which is useful for meeting the needs of content that display information in the form of visual maps and locations. The Phoca Maps and MX Maps extensions are two of the many map and location extensions available on the Joomla Extension Directory website, downloadable and widely used. This study aims to provide a reference for Joomla CMS users in terms of managing content related to maps and locations through empirical studies of the performance of Phoca Maps and MX Maps extensions. In measuring extension performance, Google Lighthouse is used to audit all quality aspects that support the performance of a web application. The research results found that, in general, the desktop and mobile performance of the Phoca Maps and MX Maps extensions was unsatisfactory. This can be seen from the performance testing results for First Contentful Paint, Speed Index, Largest Contentful Paint, Time to Interactive, Total Blocking Time, and Cumulative Layout Shift.